Vulnerabilidades - gradientes de nitidez e invisibilidade: confabul[ações] [in]comuns - Heman, Marília Rodrigues Lopes (2024)
This Doctoral Thesis is associated with the Postgraduate Program in Education of the Education Center of the Federal University of Santa Maria, with the Line of Research LP3 – Special Education, Inclusion and Difference, and with GEPE – Group of Studies and Research in Education and Inclusion, and it has as its theme the expansion and extension of a discursive matrix of vulnerability, in times of in/exclusion. The issue to be investigated was framed by the following question: What is the capillarity in expansion and extension that the discursive matrix of vulnerability [and production of the subject] has in and with the production of historical discourses, as well as political, theoretical, scientific, statistical, social-media ones, and other forms of knowledge? And, as general aim: To analyze how the discourses of a matrix of vulnerability expand and extend through the capillarity of knowledge, generating gradients of clearness and invisibility of vulnerability [and of the vulnerable subjects]. The main focus of this dissertation is on how the matrix is being produced in the scope of discourse categories, even if subjects are produced from it, with it, and/or by it. However, this is not to put in the centrality of the discursive matrix an identification/answer of a vulnerable subject, but to have the possibility of expanding and extending its variation. The methodological steps on the investigative way were taken by means of a searching activity of/in/to the production of the materialization of the research – with the production of data – from a first movement which was compositional-analytical, as the methodological procedure one: by retaking – and specific cuts – of macro-political political-legal documents; by approximation to official data from statistical materials made available by the Federal Government of Brazil; through the capture of social media posts [and media]; and then by means of a more specific experimentation, constituting the investigative action of this dissertation, from a second compositional-analytical movement, of cartography of discursive elements, as methodological procedure two: in the addresses to the missive-graphy (and to the dissertation) by means of the invitation to partners of thinking [of/in the research] from several fields of knowledge. Thus, already in the production of data – the materialization of the research – the course that formed the analytical substrate, in turn, established the two analytical unities: social risk (the clearness); and in/exclusion (the invisibility); and operators as conceptual notions to compose the analytical development of this investigation: biopolitics; and inclusion, from which two possible specific objectives have arisen, to map discursive elements, which made it possible to address two analytical focuses: the clearness of vulnerability; and the invisibility of vulnerability, for the [im]possibility of confabulation and tackling the expansion and extension of the discursive matrix of vulnerability [and production of subject], in times of in/exclusion. Therefore, this dissertation was systematized, showing that by the capillarity of knowledge, the discourses of matrix of vulnerability expand it and extend it, allowing then an intelligibility as a discursive matrix that makes vulnerability [and the vulnerable subjects] into a gradient, which is [in]visible, sometimes clear, sometimes not. Still, this research shows a discursive matrix of vulnerability [and production of subject] extensive and expansive, in which anyone can be vulnerable, and which operates by inequality under invisibility of vulnerability as ‘the epiphany of lack’ and its personification: lack/absence/impotence/negligence.